2013
DOI: 10.1021/jm301522m
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Cancer Stem Cell-Based Activity of Substituted 5-Morpholino-7H-thieno[3,2-b]pyran-7-ones Designed as Next Generation PI3K Inhibitors

Abstract: Dysregulation of the phosphatidylinositol-3-kinase (PI3K) pathway in a wide range of tumors has made PI3K a consensus target to inhibit as illustrated by more than 15 inhibitors now in clinical trials. Our previous work, built on the early pioneering multikinase inhibitor LY294002, resulted in the only PI3K vascular-targeted PI3K inhibitor prodrug, SF1126, which has now completed Phase I clinical trials. This inhibitor has properties that impart more in vivo activity than should be warranted by its enzymatic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 44 publications
1
44
0
Order By: Relevance
“…We have previously shown that 5-morpholino-7H-thieno[3,2-b]pyran-7-one (TP-scaffold) represents a promising class of PI3K inhibitors: Screening a panel of >200 kinases, we found that SF2523 is a highly selective and potent inhibitor of PI3K, particularly of the α isoform of PI3K (PI3Kα) (30). To assess SF2523 activity in the cellular context, we examined the effect of this compound on the PI3K signaling pathway in a neuroblastoma SKNBE2 cell line.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that 5-morpholino-7H-thieno[3,2-b]pyran-7-one (TP-scaffold) represents a promising class of PI3K inhibitors: Screening a panel of >200 kinases, we found that SF2523 is a highly selective and potent inhibitor of PI3K, particularly of the α isoform of PI3K (PI3Kα) (30). To assess SF2523 activity in the cellular context, we examined the effect of this compound on the PI3K signaling pathway in a neuroblastoma SKNBE2 cell line.…”
Section: Resultsmentioning
confidence: 99%
“…Normal rabbit IgG, protein A/G agarose beads, Cyclin D1, and MYC antibodies were from Santa Cruz Biotechnology, and anti-BRD4 antibody was obtained from Bethyl Laboratories. SF2523 and SF2535 were synthesized as described (30), and synthesis of SF2558HA will be reported elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…PI-103, BKM120, and PF4691502 were purchased from Selleck chemicals. SF2523 and SF1126 were obtained from SignalRx Pharmaceuticals (29,30 0 -diamidino-2-phenylindole (DAPI), hyaluronidase type V, and DNase I were from Sigma.…”
Section: Antibodies and Reagentsmentioning
confidence: 99%
“…2B). In addition to pan-PI3K inhibitors in clinical trial, we used SF2523, a novel pan-PI3K inhibitor developed in collaboration with SignalRx Pharmaceuticals (30), to see the effect of this PI3K inhibitor on HIFa stabilization. SF2523 blocked accumulation of HIF1a and HIF2a in dose-dependent manner (Fig.…”
Section: Inhibition Of Pi3k/akt Pathway Blocks the Hypoxic Induction mentioning
confidence: 99%
“…9) Subsequent PI3K phosphorylate the 3′-hydroxyl group of phosphatidyl inositol 4,5-bisphosphate (PIP2) to generate phosphatidyl inositol 3,4,5-triphosphate (PIP3), which lead to activation of downstream signaling pathways. 10) The cellular levels of PIP3 are negatively regulated by phosphatase and tensin homolog deleted from chromosome 10 (PTEN), which is a phosphatase that converts PIP3 back to PIP2. 11,12) PI3K and PTEN are contradictory of oncogenic signaling.…”
mentioning
confidence: 99%